Dynamics of Muslim Adolescent Aggression: The Relationship Between Religiosity and Aggression and Peer Religion as Moderator - Isnaini, Nurul; Suhandi, Suhandi; Pradana, Satria Adi (Universitas Islam Negeri Raden Intan Lampung, 2025)
Adolescence is a critical period marked by significant physical, cognitive, and socio-emotional changes. In Indonesia, adolescent’s aggression is a problem influenced by various factors, such as internet addiction, poor emotional regulation, anxiety, peers influence, and parenting styles. Therefore, during this period, relationships with peers become increasingly important as young people strive to be independent and have a sense of belonging. The study population of 238 people was obtained through an initial questionnaire collected on July 25, 2024 - August 20, 2024. The use of covariance-based SEM with parametric assumptions that the research variables must meet the assumption of a normal multivariate distribution. However, the research variables did not meet the assumption of normality, so Partial Least Square (PLS) was used. The hypothesis testing method used Structural Equation Modeling (SEM) with SmartPLS 4.00 software. The dynamics of Muslim adolescent aggression, especially the relationship between peer religiosity and aggression, is a multifaceted topic. General research shows that religiosity acts as a protective factor against aggression and delinquency among adolescents. However, peer influences and social context can significantly modulate this relationship.Keywords: Aggression, Religiosity, Peer Religion, Structural Equation Modeling